2008
DOI: 10.1001/jama.299.5.547
|View full text |Cite|
|
Sign up to set email alerts
|

Atherosclerotic Plaque Composition and Occurrence of Restenosis After Carotid Endarterectomy

Abstract: ESTENOSIS IS A DRAWBACK OF catheter-based and surgical interventions in different vascular territories. In coronary and peripheral artery disease, diabetes has been associated with increased development of restenosis. 1-4 In addition, following carotid artery interventions, smoking, age, and female sex have been reported as independent predictors of luminal renarrowing. 5-8 Furthermore, angiographic lesion characteristics, such as lesion length and decreased vessel diameter, are associated with increased risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…Previous studies have reported a correlation between small lipid core and development of ipsilateral restenosis after CEA [9,10]. The results of our study could therefore underline that atherosclerosis is a generated disease of the vascular system [20,21], by showing risk factors for development of stenosis of the carotid artery that are similar to risk factors for ipsilateral stenosis, as found in previous studies.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Previous studies have reported a correlation between small lipid core and development of ipsilateral restenosis after CEA [9,10]. The results of our study could therefore underline that atherosclerosis is a generated disease of the vascular system [20,21], by showing risk factors for development of stenosis of the carotid artery that are similar to risk factors for ipsilateral stenosis, as found in previous studies.…”
Section: Discussionsupporting
confidence: 88%
“…Especially, SMCs are components of a stable plaque phenotype, characterized by less inflammation and lower lipid content [22]. Earlier studies reported that removal of a stable atherosclerotic plaque gives more restenosis 1 year after follow-up [9,14]. In our study, removal of a stable plaque gives more contralateral stenosis, which suggests again that vascular disease is more extensive than only in the operated artery.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…This indicates that women have a relatively thicker carotid arterial wall. One explanation might be a different composition of the arterial wall in women which might preclude a different plaque phenotype in later life than men [36]. Our data warrant further investigation.…”
Section: Discussionmentioning
confidence: 78%